Training Need Analysis For Developing People: A Case Study of Market Development Division in PT XYZ - Firdaus, Aditya Reza; Sensuse, Dana Indra (International Journal of Artificial Intelligence Research, 2024)
The impact of Industry 4.0 on the Indonesian stock market, with a special focus on PT XYZ. PT XYZ has experienced a significant surge in individual investors, particularly from the younger generation, who are technologically savvy and prefer the stock exchange as an investment method. This paper discusses the critical role of the Market Development Division at PT XYZ in meeting the educational needs of prospective investors and companies planning to list. One significant challenge identified is the knowledge gap within PT XYZ, especially between employees with varying levels of experience, and the absence of a centralized knowledge repository. This gap hinders education for potential investors and listed companies, thereby impacting service quality. In response, PT XYZ acknowledges the need to enhance Knowledge Management (KM) practices and begins developing a tailored knowledge sharing strategy. This strategy aims to bridge the existing knowledge gap and prevent knowledge loss, utilizing the Zack Framework for gap analysis. Qualitative research methods, including semi-structured interviews with 3 experts, were employed in this study. It resulted in a gap analysis between the current state and PT XYZ's necessary knowledge regarding the implementation of knowledge sharing, leading to the recommendation of eight knowledge sharing strategies.